(untitled) (Abhat Journal, 2025)
Ethics remain a fundamental pillar of humanity and a major concern for all thinkers and philosophers, as it is the enduring essence of life. As such, the need to reflect on it continues, especially in light of the rapid developments witnessed in every era. With the significant advancements in technology today and the emergence of artificial intelligence as a reliable tool in various areas of life, ethics emerges as one of the greatest challenges facing this new system. The problematic aspect of this research lies in the ethical challenges associated with artificial intelligence. It is well known that ethics are linked to humans as responsible for their actions. However, with the presence of an intelligent "machine," the question of whether this machine possesses ethical principles that guide its behavior and enable it to perform ethical actions similar to those performed by humans begins to be raised. Therefore, this study seeks to determine whether artificial intelligence possesses ethical principles capable of directing it towards ethical action. It also aims to shed light on the extent to which artificial intelligence is capable of making ethical decisions. Furthermore, the study addresses ethical questions related to privacy, security, and the responsibility that arise from the use of these intelligent machines. The study’s revealed some significant which can be summarized as follows: a) ethics is a fundamental and pivotal element in the development of artificial intelligence, given its role in enhancing the value of the technology and ensuring its safe use, free from behavioral deviations: b) artificial intelligence has a superior ability to collect information and analyze data, but it poses a threat to ethical values ​​and principles if used in an uncontrolled manner